Biotechnologická produkce PHA z odpadních otrub - Guziurová, Pavlína (Vysoké učení technické v Brně. Fakulta chemická, 2022)
Bakalářská práce se zabývá biotechnologickou produkcí polyhydroxyalkanoátů (PHA) z odpadních pšeničných otrub. Cílem bylo zjistit, zda hydrolyzát z pšeničných otrub podrobený různým typům předúpravy lze využít jako substrát pro produkci PHA pomocí vybraných bakteriálních kmenů. Vybrané kmeny byly Halomonas organivorans, Halomonas halophila a dva kmeny Schlegelella thermodepolymerans. Za nejlepší producenty byly vybrány halofilní kmeny, se kterými byly následně provedeny další kultivace. Nejefektivněji byly bakteriemi využity hydrolyzáty po neutrální předúpravě, jelikož měly nejnižší obsah mikrobiálních inhibitorů (fenolických látek), a bakterie na nich produkovaly nejvíce PHA. Nejvyšší hodnota naprodukovaného PHA bylo na hydrolyzátu s neutrální předúpravou u kmene Halomonas organivorans, konkrétně 2,82 g/l. Hydrolyzát byl využit i pro produkci kyseliny mléčné, pro kterou byly využity bakteriální kmeny Lactobacillus. Nejvyšší dosažená koncentrace naprodukované kyseliny mléčné byla 16,73 g/l u kmene Lactobacillus casei.

The bachelor thesis deals with the biotechnological production of polyhydroxyalkanoates (PHA) from lignocellulosic waste – wheat bran. The aim was to determine whether the hydrolysate from wheat bran subjected to different types of pretreatment could be used as a substrate for the production of PHA using selected bacterial strains. The selected strains were Halomonas organivorans, Halomonas halophila and two strains of Schlegelella thermodepolymerans. Halophilic strains were proved as the best producers and were subsequently used for cultivations. The hydrolysates after neutral pretreatment were utilized by the bacteria most efficiently, due to the lowest content of microbial inhibitors (phenolic substances) where the bacteria produced the most PHA. The highest value of produced PHA was determined on the hydrolysate after neutral pretreatment by using the strain Halomonas organivorans, namely 2,82 g/l. The hydrolysate was also used for the production of lactic acid bacterial strains of Lactobacillus. The highest achieved concentration of produced lactic acid was 16,73 g/l by the Lactobacillus casei strain.
Biotechnological production of polyhydroxyalkanoates on wheat bran
Keywords: Polyhydroxyalkanoáty; polyhydroxybutyrát; pšeničné otruby; halofilní mikroorganismy; Halomonas organivorans; Halomonas halophila; Polyhydroxyalkanoates; polyhydroxybutyrate; wheat bran; halophilic microorganisms; Halomonas organivorans; Halomonas halophila